Serum B cell activating factor (BAFF) and sarcoidosis activity - Kamila HASHEMZADEH; Maryam FATEMIPOUR; Seyede ZAHRA MIRFEIZI; Mohammadhasan JOKAR; Zhaleh SHARIATI SARABI; Mohammad-Reza HATEF FARD; Houshang RAFATPANAH; Mandana KHODASHAHI (Archives of Rheumatology, 2021)
Objectives: This study aims to determine the relationship between the severity of sarcoidosis and serum B-cell activating factor (BAFF) concentrations. Patients and methods: This cross-sectional study was conducted between December 2015 and March 2018 on 55 patients with sarcoidosis (16 males, 39 females; mean age, 39.9; range 25 to 60 years) and 28 healthy subjects (7 males, 20 females; mean age, 39; range 25 to 60 years). The sarcoidosis patients were divided into active chronic sarcoidosis and acute sarcoidosis groups. The diagnosis of sarcoidosis was based on clinical, radiological, and pathologic findings. Also, the diagnosis of the active disease was based on the level of angiotensin-converting enzyme, active skin, eye, and lung lesions. Scadding score was also measured, and other patient information was collected by pre-designed questionnaires. Results: The most involved organs were the skin (92.7%) and joints (92.3%), respectively. The mean BAFF concentration in both active chronic sarcoidosis (p=0.001) and acute sarcoidosis (p=0.001) groups was significantly higher than the control group, but the mean level of BAFF in these two groups was not significantly different (p=0.351). Between two groups of patients, only calcium (p=0.001) and forced vital capacity (p=0.021) were higher in the acute group of sarcoidosis. Also, among the factors associated with active chronic sarcoidosis and acute sarcoidosis, none was significantly correlated with BAFF. Conclusion: Serum BAFF concentration was higher in patients with sarcoidosis, while this was not significantly different from increasing severity of symptoms. There was no significant difference in BAFF levels between acute sarcoidosis and active chronic types.